New record of Argemone ochroleuca Sweet (Papaveraceae) for the flora of Libya - El-Ahamir , Sh-Hoob Mohamed; Imohammed, Khaleefah Salem (Biodiversity: Research and Conservation, 2025)
Argemone ochroleuca Sweet, Brit. Fl. Gard. Ser.1 3(2): pl. 242 (1828) of the family Papaveraceae is reported here for the first time from Libya. This species is native to Mexico. Flowering specimens of A. ochroleuca were collected from the region Ariggiba (26°35’11.8”N 13°29’24.8”E), 110 km southwest of the city of Sabha, which lies about 700 km south of Tripoli. It is presented with updated nomenclature, taxonomic description, geographical distribution, key to genera, location in Libya, and colour photographs taken in the field. The voucher specimens are deposited in the Herbarium of Botany Department (ULT), University of Tripoli, Libya.